Arabidopsis thaliana DGAT3 is a [2Fe-2S] protein involved in TAG biosynthesis. Issue 1 (December 2018) - Aymé, Laure; Arragain, Simon; Canonge, Michel; Baud, Sébastien; Touati, Nadia; Bimai, Ornella; Jagic, Franjo; Louis-Mondésir, Christelle; Briozzo, Pierre; Fontecave, Marc; Chardot, Thierry
Abstract Acyl-CoA:diacylglycerol acyltransferases 3 (DGAT3) are described as plant cytosolic enzymes synthesizing triacylglycerol. Their protein sequences exhibit a thioredoxin-like ferredoxin domain typical of a class of ferredoxins harboring a [2Fe-2S] cluster. TheArabidopsis thaliana DGAT3 (AtDGAT3; At1g48300) protein is detected in germinating seeds. The recombinant purified protein produced fromEscherichia coli, although very unstable, exhibits DGAT activityin vitro . A shorter protein version devoid of its N-terminal putative chloroplast transit peptide, Δ46AtDGAT3, was more stablein vitro, allowing biochemical and spectroscopic characterization. The results obtained demonstrate the presence of a [2Fe-2S] cluster in the protein. To date, AtDGAT3 is the first metalloprotein described as a DGAT.